EFEKTIVITAS PENYELENGGARAAN PENGABDIAN PADA MASYARAKAT DI DESA CITAPEN KECAMATAN CIHAMPELAS KABUPATEN BANDUNG BARAT - Dawous Gilang Gumilang; Nurlaela Nurlaela (Jurnal Al Maesarah, 2022)
Activities to conduct community service in Citapen Village, Cihampelas District, West Bandung Regency, went smoothly. The planning process begins by creating a work program in the fields of religion, health and education designed according to the needs of the surrounding community. The process of community service is carried out in emergency PPKM so that it pays attention to strict health protocols, this becomes an obstacle because there are several programs that are effective due to limited resources. The evaluation process of community service implementation runs smoothly, judging by the enthusiasm of the community who want to participate and the LPPM who provides a good category in the process of organizing community service in Citapen Village, Cihampelas District of West Bandung Regency.